Elaiophores in three Neotropical Malpighiaceae species: a comparative study - Possobom, Clivia C. F.; Machado, Silvia R. [UNESP] (Springer Nature, 2018)
Malpighiaceae species are recognized for their sepal elaiophores of which secretions reward oil-collecting bees. Information on elaiophore location, structure and functioning is likely to provide valuable insights into pollination ecology and evolution of the family. We characterized the elaiophores in three Malpighiaceae species and compared the patterns of distribution and dimensions of these glands, their structural organization, their histochemistry and their life spans. Intact elaiophores from buds and 1-day flowers (bagged and un-bagged) of Banisteriopsis variabilis, Byrsonima coccolobifolia and Peixotoa reticulata were collected for structural, histochemical and ultrastructural studies. We also reported the behavior of elaiophore-visiting insects. Elaiophores exhibit uniseriate secretory epithelium covered by a thick cuticle and vascularized parenchyma. The secretory surfaces can be flat (B. coccolobifolia and P. reticulata) or convoluted (B. variabilis). In B. variabilis and P. reticulata the epithelium has longer cells than in B. coccolobifolia and these become papillose, taking an appearance similar to trichomal elaiophores. The mixed secretions accumulate within subcuticular spaces and may be released either by a natural rupture of the cuticle (B. coccolobifolia and P. reticulata) or by a sudden rupture caused by the bee activity (B. variabilis). Different bees were observed exploiting the elaiophores, acting as potential pollinators or oil robbers. A greater diversity of oil-collecting bees was registered in B. variabilis. The differences identified, mainly in relation to the location of the glands on the sepals, in the fine structure of secretory epithelia and cuticle architecture, and in their secretion release mechanisms, in some way, can affect the behavior of visitors.
Keywords: Banisteriopsis; Byrsonima; Electron microscopy; Light microscopy; Oil secretion; Peixotoa